INTEGRATION, RELATION, AND RECREATION: RETHINKING ARCHITECTURAL PROGRAMMING - Redyantanu, Bramasta Putra (Journal of Architecture&ENVIRONMENT, 2025)
This study rethinks architectural programming as an innovative process, emphasizing the integration of contextual elements, the relational blending of multiple functions, and the adaptive reuse of existing spaces as recreation over time. Moving beyond the traditional understanding of programming as problem-finding-solving, this research redefines it as a dynamic framework bridging theoretical insights and practical design applications. Through a qualitative case study methodology, the paper examines three landmark projects with similar functions by Bjarke Ingels Group—8 House, The Mountain, and Urban Rigger—to explore the transformative potential of programming. The analysis positions programming as an integrative tool that aligns spatial, functional, and contextual dynamics to address both immediate and future architectural challenges. Program mixing with relational functions is conceptualized as a strategic approach that harmonizes diverse functions within a single design, fostering innovative and hybrid solutions. Adaptive reuse, reframed as a multi-time design response, focuses on revitalizing existing structures to meet evolving societal and environmental needs. These case studies illustrate how programming establishes a dynamic framework that enables architects to creatively reimagine constraints as opportunities. By emphasizing the principles of design analysis—realization, organization, and integration—this research contributes to the discourse on programming as a catalyst for architectural innovation and transformation. It proposes a shift in practice that highlights programming as a generative and responsive framework, inspiring a rethinking of architectural methodologies in the face of contemporary challenges.